ASSIMILATION IN AMY TANS THE KITCHEN GODS WIFE - Subur Laksmono Wardoyo (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
Assimilation of Chinese Americans may take the mode of China Doll, Anglo Conformity, or Cultural Pluralism. Each of those three modes appears in The Kitchen Gods Wife in the way the main character starts out as a China Doll, turns into some sort of Anglo Conformity, and finally assumes an attitude of Cultural Pluralism.